Political economy of the air quality management of Nairobi city - Washington Kanyangi; Joanes Atela; George Mwaniki; Tom Randa; Humphrey Agevi; Humphrey Agevi; Eurallyah Akinyi (Frontiers in Environmental Health)
Poor urban air quality is a growing global concern due to its far-reaching environmental, social, and health impacts. Nairobi City's rapid urbanization—characterized by rising human and vehicular populations, industrial expansion, and commercial activities—has significantly deteriorated air quality. Despite the existence of international, national, and county-level policies on air quality management, their implementation remains weak due to overlapping mandates, unclear institutional roles, and limited capacity. This study analyzed Nairobi's sectoral sources of air pollution, governance structures, and strategic entry points for gender-responsive air quality management. Using a mixed-methods approach, in addition to the policy analysis and urban diagnostics, the study finds that air pollution in Nairobi is driven by multiple interconnected sectors, necessitating a coordinated and cross-sectoral approach. While existing institutions play key roles, an integrated Nairobi Air Quality Working Group is essential for harmonizing policy efforts, strengthening enforcement, and fostering inclusive governance. The findings highlight the need for a streamlined regulatory framework, enhanced institutional coordination, and targeted capacity-building programs to address air pollution effectively and equitably.